Pre-service Mathematics Teachers’ Belief towards Mathematics; A Confirmatory Factor Analysis - Linguistika, Yulia; Darmawan, I Gusti Ngurah (Faculty of Education Universitas Negeri Malang, 2021)
The purpose of the study was to assess the construct validity and reliability of pre-service mathematics teachers’ belief towards mathematics. The analysis of this study started by proposing four alternative models. The alternative models were compared to obtain the best fit model and its validity and reliability were evaluated by looking at the factor loadings and the proportion of variance. Based on the factor loadings, the hierarchical model has moderate standardised structure coefficients from 0.272 to 0.658 which indicates that they have the stronger indication that the factors represent the unobserved construct. However, due to the model fit and the structure coefficients which are close and greater than 0.4, three factors reflecting the Teachers’ Beliefs about Mathematics construct were retained for further investigation.